A microfluidic cartridge for fast and accurate diagnosis of Mycobacterium tuberculosis infections on standard laboratory equipment. Issue 8 (24th February 2021) - Homann, Ana R.; Niebling, Laura; Zehnle, Steffen; Beutler, Markus; Delamotte, Lubov; Rothmund, Marie-Christine; Czurratis, Daniel; Beller, Klaus-Dieter; Zengerle, Roland; Hoffmann, Harald; Paust, Nils
Abstract : We present a novel centrifugal microfluidic approach for fast and accurate Tuberculosis (TB) diagnosis based on the use of standard laboratory equipment. Abstract : We present a novel centrifugal microfluidic approach for fast and accurate tuberculosis (TB) diagnosis based on the use of standard laboratory equipment. The herein presented workflow can directly be integrated into laboratories with standard equipment and automates complex sample preparation. The system consists of a microfluidic cartridge, a laboratory centrifuge and a standard PCR cycler. The cartridge includes all required reagents and automates collection of bacteria on filter membranes, bacterial lysis, nucleic acid extraction and aliquoting of the DNA extract for PCR analysis. We show that storage of the reagents in aluminium-coated pouches is stable during accelerated storage and transport tests. When the limit of detection was assessed, we found that the cartridge-automated workflow consistently detected 10 CFU ml −1 of mycobacteria in spiked sputum samples. First tests with clinical samples showed a 100% specificity for non-TB specimens. In addition, Mycobacterium tuberculosis (MTB) was re-found in pre-characterized smear microscopy and culture positive sputum samples suggesting a high diagnostic sensitvity. In summary, the novel cartridge-automated workflow enables a flexible and sensitive TB diagnosis without the need to invest in specialized instrumentation.